AI software/hardware as mind/body problem - Čufar, Kristina (Zbornik znanstvenih razprav (Pravna fakulteta. 1991), 2024)
Artificial intelligence (AI) and other algorithm-based technologies have become part of everyday life over the last decade. While AI holds amazing potential and has already contributed positively to the human condition, it is also subject to fierce critique as it may, for example, reproduce bias and social injustices or increase dystopic forms of surveillance. While most scholarly, regulatory, and ethical debates focus on AI software-related issues, AI hardware receives far less attention. Understanding AI as software, as an artificial mind, highlights only the supposedly new and exciting aspects of this technology and ignores the human and material costs of its fabrication. This is consistent with the traditional mind-body dualism, which prioritises mind over body and thus skews our perception of the problem. To counter the dominant narratives, this article proposes a concept of AI as hardware/software to broaden the scope of ethical and legal issues that ought to be addressed through AI regulation. A holistic and systemic treatment of the AI phenomenon robs it of its perceived uniqueness. Once the worldwide extraction of materials, labour, and data necessary to set up AI machinery is seriously considered, AI stands out as yet another instance of colonial capitalism.
Keywords: artificial intelligence; colonialism; človekove pravice; ethics; etika; human rights; kolonializem; umetna inteligenca